Studies on Oxovanadium (IV) Complexes with 4-[(N-Acetyl) Amino]-Antipyrine †. - K. AGARWAL, R.; SINGH ., GYANENDRA (Asian Journal of Chemistry, 2010)
Oxovanadium (IV) complexes of 4-[(N-acetyl) amino] antipyrine (AAAP) having the composition [VO(AAAP)X2] (X ═ Cl, Br, I, NO3, NCS or 0.5C2O4) and [VO(AAP)2] (ClO4)2 have been synthesised and characterised. The probable C.N. of V(IV) is found to be five.